2022
DOI: 10.3390/gels8110707
|View full text |Cite
|
Sign up to set email alerts
|

Prestressed Composite Polymer Gels as a Model of the Extracellular-Matrix of Cartilage

Abstract: Articular cartilage is a composite hydrogel found in animal and human joints, which exhibits unique load-bearing properties that have been challenging to reproduce in synthetic materials and model in molecular dynamics (MD) simulations. We computationally investigate a composite hydrogel that mimics key functional properties of articular cartilage as a potential biomimetic model to investigate its unique load-bearing properties. Specifically, we find that the emergence of prestress in composite gels derives pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Molecular dynamics simulations have shown that tethered aggrecan molecules exhibit strong mutual repulsion and interpenetrate to a very limited extent when forced together. 35–38 These calculations also showed that in the physiological pH range the aggrecan molecules are separated but that interpenetration increases at high concentrations of monovalent salt. 39 Recent experimental studies on aggrecan solutions, made by small angle neutron, X-ray and light scattering, confirmed the absence of significant penetration among the aggrecan bottlebrushes, and also revealed that both the structure and dynamics of aggrecan assemblies are largely insensitive to ionic strength, even in the presence of higher valence counter-ions.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Molecular dynamics simulations have shown that tethered aggrecan molecules exhibit strong mutual repulsion and interpenetrate to a very limited extent when forced together. 35–38 These calculations also showed that in the physiological pH range the aggrecan molecules are separated but that interpenetration increases at high concentrations of monovalent salt. 39 Recent experimental studies on aggrecan solutions, made by small angle neutron, X-ray and light scattering, confirmed the absence of significant penetration among the aggrecan bottlebrushes, and also revealed that both the structure and dynamics of aggrecan assemblies are largely insensitive to ionic strength, even in the presence of higher valence counter-ions.…”
Section: Introductionmentioning
confidence: 89%
“…Aggrecan molecules and their complexes behave like microgels, i.e., under external loading and unloading they release and reabsorb fluid rapidly and reversibly. 35,36,[40][41][42] In this work we investigate the structure and dynamics of the main cartilage polymers at their different hierarchical levels of organization to analyze how they contribute to cartilage's biomechanical properties. The bristles in aggrecan are composed of linear GAG chains, chondroitin sulfate (CS) and keratan sulfate, tethered along the extended central protein core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with gradual increments in the value of λ, a systematic decline in solvent quality ensues, owing to the introduction of attractive forces among the polymer chain. This method has previously proven effective in characterizing star polymers and gels while exploring conformational behaviors under different solvent conditions 47–49 . It should be noted that these forcefield parameters are implemented to qualitatively describe the approximate molecular structure informed from the experimentally studied CPs.…”
Section: Models and Methodsmentioning
confidence: 99%
“…This method has previously proven effective in characterizing star polymers and gels while exploring conformational behaviors under different solvent conditions. [47][48][49] It should be noted that these forcefield parameters are implemented to qualitatively describe the approximate molecular structure informed from the experimentally studied CPs.…”
Section: Model Descriptionmentioning
confidence: 99%